Optimization of Task Force 115 with the Coordination Model of Central and Regional Task Forces as a Form of Illegal Transshipment Prevention in Indonesia - Salsabila, Aldhanalia Pramesti (Lex Scientia Law Review, 2018)
Illegal fishing that is currently rife has prompted Minister Susi Pudjiastuti to implement a system of sinking ships in accordance with what has been regulated by law. The formation of Task Force 115 has also been formed to deal with illegal fishing practices, but these regulations have not deterred foreign vessels. As a result of this firmness against illegal fishing, foreign vessels have changed their mode by utilizing local fishermen who are funded. Big foreign ships or what we can call mafia waiting on the high seas, where no country controls the sea. Then after the cooperating fishermen have finished catching fish, it will be handed over to the foreign ship that ordered them. The term for this act is transhipment. Task Force 115 is tasked with developing and implementing law enforcement operations in an effort to eradicate illegal fishing in the Indonesian jurisdictional sea area in an effective and efficient manner by optimizing the utilization of operational personnel and equipment, including ships, aircraft and other technology owned by agencies/agencies who have joined it.